Rancang Bangun Sistem Informasi Pendaftaran Pembuatan Surat Izin Mengemudi Berbasis Web - M Fajar Riansyah; Suendri Suendri (JURIKOM (Jurnal Riset Komputer), 2022)
Police have a very important role in society. The main task and function of the police in protecting the community is the main thing to do in order to create order in society. The traffic police currently acts as a service that takes care of making a driving license (SIM). So far, SIM registration is still done manually by police officers. Therefore, the applicant must go directly to the Deli Serdang Police Traffic Unit to register and fill out the form, then the officer will enter the applicant's data individually. So it must require higher accuracy for officers when entering applicant data, then it can result in long queues for applicants and can take longer. To assist officers in managing applicant data and avoid long queues. So a website-based driving license registration information system was built. With the creation of this system, it is hoped that it can be the best alternative for the Deli Serdang Police Traffic Unit officers in improving performance, especially in terms of services for managing a driving license (SIM). So that there are no longer queues that are so long and applicant files that accumulate in the archive warehouse. In building this system the author uses MYSQL as a database, PHP and HTML as a programming language, and uses the waterfall method in designing and formulating problems